Cover Feature: Silylene‐Bridged Tetranuclear Palladium Cluster as a Catalyst for Hydrogenation of Alkenes and Alkynes (ChemCatChem 1/2021). Issue 1 (7th December 2020) - Yanagisawa, Chikako; Yamazoe, Seiji; Sunada, Yusuke
Abstract : The Cover Feature depicts a planar tetranuclear palladium cluster having bridging organosilylene ligand, which shows good catalytic performance in the hydrogenation of alkenes and alkynes. In their Communication, C. Yanagisawa et al. explain that a planar tetranuclear palladium cluster, synthesized by the reaction of the palladium(0) precursor [Pd(CN t Bu)2 ]3 with cyclotetrasilane via insertion of palladium species into the Si−Si bonds, acts as an efficient catalyst for the hydrogenation of alkenes and alkynes, including sterically hindered tri‐ and tetra‐substituted alkenes. More information can be found in the Communication by C. Yanagisawa et al.